2012
DOI: 10.1063/1.4768293
|View full text |Cite|
|
Sign up to set email alerts
|

A combined first principle calculations and experimental study on the spin-polarized band structure of Co-doped PbPdO2

Abstract: With x-ray spectroscopy and first-principles calculations, we expose the electronic structure, near the Fermi level, of Co-doped PbPdO2 composed of O 2p-Pd 4d hybridized states with an additional contribution of a spin-polarized Co 3d state at either a greater or smaller energy. The spin-polarized Co 3d states interacting with O 2p-Pd 4d hybridized states cause spin splitting at the band edge. Fascinating physical properties such as high-temperature ferromagnetism thus arise in Co-doped PbPdO2. Results will he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It is suggested that the localized Co would be responsible for the large band gap of 0.35 eV for the PbPd 0.75 Co 0.25 O 2 bulk material. Interestingly, our calculated results were consistent with the reported results [ 23 ]. The band gap of PbPdO 2 slab was slightly larger than that reported in our previous calculated work because of the different full in-plane structure relaxation [ 14 ].…”
Section: Resultssupporting
confidence: 93%
“…It is suggested that the localized Co would be responsible for the large band gap of 0.35 eV for the PbPd 0.75 Co 0.25 O 2 bulk material. Interestingly, our calculated results were consistent with the reported results [ 23 ]. The band gap of PbPdO 2 slab was slightly larger than that reported in our previous calculated work because of the different full in-plane structure relaxation [ 14 ].…”
Section: Resultssupporting
confidence: 93%
“…13) and Co-doped PbPdO 2 (Ref. 16) have been realized experimentally, and the experimental Curie temperature of Mn 2 CoAl is 720 K. 13 Motivated by the relation between HM-FMs and SGSs (Figs. 1(a) and 1(b)), very recently, Du et al 17 proposed a class of materials: gapless (also known zero-gap) HM-FMs.…”
mentioning
confidence: 99%
“…[35][36][37] Surprisingly, some of those have been realized experimentally. 37,38) Next, we consider the effect of strain on the physical properties of ferromagnetic MATMI 3 . The strain is defined as ε = (a − a 0 )=a 0 , where a and a 0 are the lattice constants of strained and nonstrained MATMI 3 .…”
mentioning
confidence: 99%